2006
DOI: 10.4067/s0717-95022006000500025
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effect of Chlorhexidine, Tap Water and Normal Saline on Healing Wounds

Abstract: Many researchers have advocated in recent times that antiseptic use in healing wounds should be discouraged. Antiseptics have been found to retard healing of wounds. Innocuous solutions like normal saline and tap water are being considered as better alternatives to antiseptics. Chlorhexidine, a commonly used antiseptic, is known to be less toxic on granulation cells. We decided to compare the effect of chlorhexidine, normal saline and tap water on healing wounds. Three groups of wistar rats had 2 by 2cm full t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 7 publications
(4 reference statements)
0
19
0
Order By: Relevance
“…This technique is used for the removal of foreign bodies, loose adhered tissues, in addition to maintaining the recently formed granulation tissue (15) . However, international studies indicate the use of potable water at room temperature, because it does not show significant indices of infection when compared with sterile saline solution (16)(17)(18) . The use of tap water for cleaning leg ulcers is also referred to by the protocols of Ireland and England (8)(9) .…”
Section: Discussionmentioning
confidence: 99%
“…This technique is used for the removal of foreign bodies, loose adhered tissues, in addition to maintaining the recently formed granulation tissue (15) . However, international studies indicate the use of potable water at room temperature, because it does not show significant indices of infection when compared with sterile saline solution (16)(17)(18) . The use of tap water for cleaning leg ulcers is also referred to by the protocols of Ireland and England (8)(9) .…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vitro studies showed that chlorhexidine negatively affected fibroblast and keratinocyte proliferation in a concentration‐ and time‐dependent manner (32–35). However, only some in vivo studies (36, 37) indicated a negative effect of chlorhexidine on wound healing, while a considerable number of studies indicated the value of chlorhexidine rinses after various oral surgical procedures and a positive effect of chlorhexidine on wound healing (1, 6, 38–44). The results of this study confirmed the positive in vivo effect of chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%
“…It is a mild but effective disinfection agent and will not harm normal tissue, unlike many stronger antiseptics. 9 It is available and less expensive in compared to PI.…”
Section: Discussionmentioning
confidence: 99%
“…8 It is accessible, non-irritant, and less expensive in contrast to PI. 9 Previous studies proposes that the mechanical cleaning of the vagina by NS solution had the same effectiveness in anticipation of postoperative infection. 10,11 This study aims to compare the difference in the rate of postoperative vaginal irritation symptoms and the rate of postoperative infections after using PI and NS solution in vaginal cleaning before office hysteroscopy.…”
Section: Introductionmentioning
confidence: 99%